COUNSELING ON DIGITAL MARKETING OPTIMIZATION TO INCREASE THE PRODUCTIVITY OF MSME BUSINESS IN RIANGGEDE VILLAGE, TABANAN - Satria, Wahyu Indra; Pratiwi, Nuning Indah; Dewi, Adeliya Puspita (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Rianggede Village is a village located in Penebel District, Tabanan Regency, Bali Province. Small business is one of the sectors that supports the economy of residents in Rianggede Village, however, there are still many small business actors who still do not understand the importance of implementing digital marketing strategies for the products they produce. Digital marketing is the activity of marketing or promoting a brand or product using digital media or the internet to attract consumers or potential customers quickly. The existence of small businesses is expected to be able to boost the economy of the villagers. With the existence of community service activities where the work program activities by conducting socialization activities related to digital marketing to small businesses in Rianggede village, Penebel sub-district, Tabanan district. This socialization activity related to digital marketing aims to make small businesses in Rianggede Village more productive, thriving, and able to compete in the digital era.